Review of the genus Exopholis Motschulsky, 1859 (Coleoptera: Scarabaeidae: Melolonthinae: Leucopholini) in the Philippines - Calcetas, Orlando A.; Adorada, Jessamyn R.; Navasero, Mario V. (Zootaxa, 2020)
Motschulsky (1859), a Russian Imperial Army Colonel and entomologist, established the genus Exopholis, described E. birmannica and transferred Melolontha hypoleuca Wiedemann, 1819 to it. Brenske (1896) described Exopholis philippinica from the “Philippinen” from a single female specimen. Dalla Torre (1912), listed eight species under the genus Exopholis Motschulsky, 1859 from South East Asia: E. hypoleuca (Weidemann, 1819) (Myanmar, Malaysia, Borneo, Java, Sumatra, Nias, Ambon), E. costata (Burmeister, 1855) (Java, Nias), E. birmanica Motschulsky, 1859 (Myanmar), E. lacordairei Waterhouse, 1867 (Borneo), E. pinguis Lansberge, 1879 (Sumatra), E. brenskei Nonfried, 1891, E. borneensis Brenske, 1894 (both from Borneo) and E. philippinica Brenske, 1896 (Philippines). This paper aims to review the taxonomy of Exopholis from the Philippines. Specifically, to focus on the diagnosis of Exopholis philippinica and its geographic distribution.